ANALISI NILAI PENDIDIKAN KEIMANAN KETAQWAAN PADA ANIME “THE JOURNEY” DAN RELEVANSINYA PADA MATERI IMAN KEPADA ALLAH - Aulia, Salma; Mufid, Mufid (Raudhah - Proud To Be Professional, 2025)
This study aims to analyze the values ​​of faith and devotion education contained in the anime film "The Journey", and its relevance to the material 'Faith in Allah" in grade 7 of junior high school. The method used in this study is content analysis to explore religious messages and moral values ​​in the storyline, characters, and dialogues of the film. The results of the analysis show that the film "The Journey" conveys various values ​​of faith and devotion education related to faith in Allah, such as signs of Allah's power, stories of the Prophets & Apostles, and the application of Faith in everyday life. This study also links these values ​​with basic competencies and learning objectives in the Islamic Religious Education curriculum at junior high school level. So it is expected to provide an alternative learning media that is interesting and relevant for students. In conclusion, "The Journey" is not only a work of entertainment art, but also a learning tool that has the potential to strengthen the faith and devotion of the younger generation.